The Frequency of Depression in Post Stroke Patients presenting at Outpatient Department of Abbasi Shaheed Hospital, Karachi: Depression in Post Stroke Patients - Sana Jabeen, Sana Jabeen; Sadia, Maimoona; Begum, Shaheena; Khan, Muhammad Nadeem Ahmed (Pakistan Journal of Health Sciences, 2023)
Post-stroke depression (PSD), is a recognized complication among of stroke survivals. Timely diagnosis and its management are particularly important in the reduction of stroke. Objective: To find out the frequency of depression in post stroke patients presenting at Outpatient Department of Abbasi Shaheed Hospital, Karachi. Methods: Cross-sectional study was carried out from 10/4/2018 to 10/9/2018. Sample size of 112 patients was calculated using the WHO software, by taking prevalence of depression 37.9 %, margin of error 9% and confidence level ‘C.l’=95%. Ischemic stroke patients who fulfil the inclusion criteria were enrolled. Short history and demographics were entered in the Performa. Screening of depression was done on BDI score. Simple descriptive statistics with mean and standard deviation were used to provide quantitative data, whereas frequency and percentages were used to convey qualitative characteristics. To determine how these factors affected the outcome variable, effect modifiers were taken into account by stratification of age, gender, marital status, occupational status, socioeconomic position, and educational status. A chi square test was used after stratification, with a p-value of 0.05 considered significant. Results: Out of 112 patients, mean age with standard deviation and duration of disease were 47.14 ± 7.49 years and 18.72 ± 3.89 months respectively. 64 (57.1%) were male and 48 (42.9%) were female. Amongst patients with ischemic stroke, 52 (46.4%) had depression and 60 (53.6%) did not have depression, furthermore marital status, level of education and smoking appeared to be link with post stoke depression. Conclusions: Stroke patients represent a significant segment of population with unrecognized depression with different underlying factors.